The characterization and antioxidant activity of chitosan-alginate nanoparticles encapsulating cymbopogon citratus and cymbopogon nardus aqueous extracts - Aimi Zafirah, Abd Rahim (2019)
This study aimed to formulate polymeric nanoparticles to encapsulate aqueous extracts of two Cymbopogon species which are Cymopogon citratus and Cymbopogon nardus that contain unstable antioxidant agent. Apart from having the nano-sized particles which may enhance penetration to the skin, nanoparticles are also known for their abilities to increase the stability of therapeutic agents by chemical or physical means, as well as to deliver higher concentrations of drugs to target areas. The aqueous extracts were obtained by three different extraction methods which are decoction, infusion and soxhlet extraction. Polymeric nanoparticles which are chitosan-alginate nanoparticles were prepared by a modified ionic gelation method and characterized for their particle size, zeta potential, polydispersity index, and encapsulation efficiency. All the formulations were also evaluated for the antioxidant activity by free scavenging DPPH assay. The polymeric nanoparticles encapsulating C. nardus aqueous extracts by soxhlet extraction were found to give satisfactory results of particle size, zeta potential, polydispersity index and encapsulation efficiency with values of 281±34.31 nm, -36.25±3.43 mV, 0.48 and 86.9±5%, respectively. All the nanoparticles formulations were found out to exhibit antioxidant activity with the highest percentage of inhibition activity of 58.29±0.34%.